Adaptation of Tea Seeds (Camellia Sinensis L.) Lowland Based on Physiological Characteristics and Growth at Suboptimal Temperatures - Adryade Reshi Gusta; Mirodi Syofian; Dedi Supriyatdi (Politeknik Negeri Lampung., 2018)
This study aims to determine the best clone species and the best dosage of Salvinia natans compost on the growth and physiological character of lowland tea. This study aims to determine the best types of clones and dosage of Salvinia natans compost for growth and physiological character of lowland tea. This study used a randomized block design experiment with three replications arranged in factorial 2x4. The first factor is a type of clones consists of two (2) levels, namely: Gambung 6 (G1) and Gambung 7 (G2). The second factor is the dosage of Salvinia natans compost with topsoil 100% (K0), topsoil and Salvinia natans compost comparison by1: 1(K1), topsoil and Salvinia natans compost comparison by2: 1(K2), dan topsoil and Salvinia natans compost comparison by3: 1(K3). All data were analyzed for the variance. Analysis followed by separation of means using LSD test with significance level of 5%. The results showed that the clones of Gambung 7 showed the higher value for observation variability in higher growth of seedlings (40,75) and better dry weight(10,78 g). Topsoil planting medium comparison by Salvinia natans compost (1: 1) showed the higher value for observation variability in higher growth of seedlings (42,25) and better dry weight (10,95 g). So, the conclusion is Gambung 7 for the best clone species on the growth and physiological character of lowland tea. The best dosage of Salvinia natans compost on the growth and physiological character of lowland tea is topsoil planting medium comparison by Salvinia natans compost (1: 1).